METAFORA PENGUNGKAP KECANTIKAN DALAM MASYARAKAT MADURA - Putri, Nur Awaliyah (ETNOLINGUAL, 2018)
Abstract This paper describes the metaphors in Madurese used for expressing women’s beauty, and the Madurese people’s prespective about women’s beauty through those metaphors. Library reasearch was conducted to obtain the data. The library research refers to the use of books containing the list of metaphors used by Madurese people to express women’s beauty. An old Madurese dictionary was also used for translating some old words found and which were no longer used in daily communication. In addition, the writer also read some references about Madurese culture to elicit more information about Madurese cultural values and practices, especially that are related to the objects used for those metaphors. Referential comparation method with classifying technique was used for analyzing the data. The data were classified based on their reference. Afterwards, the writer compared the object used in the metaphors, and the woman’s physic and behaviour. The results showed that there were 49 metaphors in Madurese used for expressing women’s beauty which consisted of 39 metaphors for women’s physical beauty, and 10 metaphors for behavioural beauty. The objects compared in the metaphors included plants, equipments, animals, food, and nature. The metaphors reflect the Madurese people’s prespectives about women’s beauty; which are: 1) women’s physical beauty is easier to be expressed in metaphor than the behavioural one; 2) woman’s behavioural beauty is very important; 3) there are more than one ideal shape of some particular women’s body parts; and 4) plant is a high source of life, culture and practice value in Madurese society.